Analisis Pengelolaan Media Pembelajaran di Sekolah Menengah Kejuruan Negeri 01 Sutera - Arista, Nadia Pransiski; Sufyarma, Sufyarma (Al-DYAS, 2024)
This study aims to analyze the management of learning media at Ngeeri 01 Sutera Vocational High School. The research conducted was using qualitative methods. In conducting this scientific research, the object of research is the State Vocational High School 1 Sutera, Pesisir Selatan Regency. The instrument or tool of this research is the researcher himself. In this study, the data sources used were person, place and paper. Based on the results of data analysis and discussion, the results of learning media management at SMK N 1 Sutera can increase student competence, improve learning quality, students are actively involved in participating actively in the learning process then learning objectives are achieved.